The Impact of Social Media on Student Morals at SDN 2 Kalikesur - Yahya, Muhammad Slamet; Munjidah, Munjidah (Arfannur, 2024)
The sophistication of technology so that everything can be available quickly is the impact of globalization. The purpose of this paper is to analyze the effects of social media on student morals. This paper uses a qualitative method with data collected through observation and interview techniques. The results of the study show that moralityis a trait that has existed since birth in his soul and has always existed in him according to his guidance, good actions are called noble morals, and bad actions are called despicable morals. The impact of social media TikTok, Youtube, Instagram, Snackvideo, and Whatsapp on the morals of SDN 2 Kalikesur students has shown a negative effect on children because of the way they speak, they often use bad words such as dogs, pigs, "sundala ”, and various other expressions.